The Role of Angiotensinogen rs699 in Diabetic Nephropathy Among Type 2 Diabetes Mellitus Patients with Uncontrolled Postprandial Glucose Levels - Anggelia Puspasari; Devy Afriyanti; Huntari Harahap; Citra Maharani; Elfiani Elfiani (Universitas Nahdlatul Ulama Surabaya, 2022)
Diabetic Nephropathy (DN) is the most common complication of Type 2 Diabetes Mellitus (T2DM), leading to the highest mortality rate of DM complications. However, its etiology is still questionable. Hyperglycemia, hypertension, and particular genetic susceptibility are associated with DN. Not all patients with uncontrolled hyperglycemia suffer DN. Thus, genetic susceptibility may be a risk factor for DN. The genetic variant of angiotensinogen rs699 is known to be associated with the risk of DN with inconsistent results between ethnicities. This study aims to reveal the correlation between the AGT rs699 with the incidence of diabetic nephropathy among type-2 diabetes mellitus patients with uncontrolled postprandial glucose levels in the Jambi Malay ethnicity. This study was observational analytic research with a cross-sectional design. It used 48 DNA samples from type-2 diabetes mellitus patients with uncontrolled postprandial glucose levels. The authors took 24 DNA samples from patients with DN and 24 without DN (as a control group). The genotyping method used ARMS-PCR specific for AGT rs699. Subjects with the CT genotype had a lower risk for diabetic nephropathy than the CC genotype, but it was not statistically significant (p=0.247; OR=0.508; 95%CI=0.160-1.607). In addition, subjects with the T allele (p=0.331; OR=0.621; 95%CI-0.237-1.630) had a lower risk for diabetic nephropathy than the C allele, but it was not statistically significant. In conclusion, Angiotensinogen rs699 is not a risk factor for diabetic nephropathy among type-2 diabetes mellitus patients with uncontrolled postprandial glucose levels in the Jambi Malay ethnicity.